If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + y = 6 + 2y Solving 8 + y = 6 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 8 + y + -2y = 6 + 2y + -2y Combine like terms: y + -2y = -1y 8 + -1y = 6 + 2y + -2y Combine like terms: 2y + -2y = 0 8 + -1y = 6 + 0 8 + -1y = 6 Add '-8' to each side of the equation. 8 + -8 + -1y = 6 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = 6 + -8 -1y = 6 + -8 Combine like terms: 6 + -8 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| -5(3t-2)+2t=4t-9 | | x^4-8x^3+98x^2-648x+1377=0 | | 36m^-4n^-6/4mn^-2p^-4 | | -x^2-100=0 | | 19=4-2m-m+7 | | (2x+4)+(3x-13)=180 | | 20a+25= | | 12-4y=2(y+9) | | 2.50x=500+0.35x | | 16a+28= | | 150x+50y=8395 | | (2a/a^2)^-2 | | 50(x+5)=a | | 200x+100y=12995 | | 3k(3k+10)=0 | | (2a/a^2)^2 | | 5x-2x=x+30 | | 3x-2=5x-19 | | 1-x=-9 | | 12a+8b= | | 7/8(16) | | 8x-4=-10x-3 | | 6(x-9)=24 | | 12x+5y=24547 | | 36w^2+39w+75=-2w-4 | | 1-6r=4-3r | | n+6=-12 | | 4(3x-2)=22 | | 39+4y-1=14y-11-3y | | 6y+8=3y+8 | | Lots(1000)=3 | | 10y-9=4y+3 |